Migrações, trajetórias, retornos: imigrantes brasileiros no Paraguai (1970-2018) - Gnoatto, Vanucia (2020)
The dissertation analyzes the migratory trajectories of Brazilian families to Paraguay and the return to Brazil, from 1970 to 2018, in the Santa Rita, Raul Peña, Naranjal and San Alberto districts, in the department of Alto Paraná and in the cities of Foz do Iguaçu, Santa Terezinha de Itaipu and Missal, in the state of Paraná, seeking to understand the networks created by these subjects throughout their migrations, and the variants linked to these migratory processes. From the study of the migratory trajectories of these subjects, it is possible to state that this is a migratory contingent resulting from multiple internal migrations in Brazil, following the advance of the agricultural frontier, starting from the old colonies to the new colonies in Rio Grande do Sul, advancing later west of Santa Catarina and Paraná, to finally cross the border, settling in eastern Paraguay. Another contingent added to this group comes from the northeast and southeast of the country, which departed from north Paraná, settling in the same place in Paraguay. What unites the two groups is the search for land access and ownership. The study seeks to locate and identify, at first, the presence of migratory networks, whether family or social. Secondly, it analyzes the insertion and readaptation of Brazilian immigrants in the place of arrival, through associative and social networks, and the definition of an element of distinction based on the use of the Portuguese language. Still, the relationship of Brazilian immigrants with land ownership and agrarian conflicts, added to the advance of agribusiness and an expansion of the agricultural frontier. As a last point, we discuss the permanence of the migratory movement, through the return of Brazilians from Paraguay, settling in the west of the state of Paraná, the networks created by these subjects that enable return migration. The study allows us to state that the advance of agribusiness was the central factor that drove the emigration from Brazil to Paraguay, and at the moment, the same process is causing much of the return to Brazil. Still, the return comes from the pursuit of education, health, social security, among other factors. In theoretical-methodological terms, it is a study of contemporary migratory movements from the use of oral history. The structure of the research documentary corpus consisted of life stories collected between Brazilian immigrants in Paraguay and the returnees, located on the bo rder between the two countries.